Habilidades Investigativas Digitales en la Resolución de Problemas de Cálculo, en Estudiantes Universitarios de Ciencia e Ingeniería en Contexto COVID-19 - Laderas Huillcahuari, Edison (2023)
The research developed deepens the impact of digital investigative skills in solving calculation problems, in university students of science and engineering of the National University of San Cristóbal de Huamanga, 2021. To do this, an applied research is addressed, research level explanatory of quasi-experimental design with pre and post-test, analytical inductive method, four samples consisting of 30 students were established, in each group the data was collected through questionnaires and virtual pedagogical test, making use of the benefits of ICT; non-parametric statistics were applied, whose contrast statistic is the H Kruskal Wallis for four independent samples with a confidence level of 95% and a significance level of 5%. Obtaining the result of the statistic H = 11.837 and p-value = 0.008 < 0.05. Consequently, the significant difference with respect to the pretest is demonstrated, so that a higher percentage of students achieved greater skill and an innovative alternative and excellent results in problem solving. Finally, the work contributes to having better results in learning to solve mathematical problems through the active management of digital investigative skills in higher education, as a challenge to the current global educational and health crisis in the face of COVID-19.